Complement Fixation Test To Assess Humoral Immunity in Cattle and Sheep Vaccinated with Brucella abortus RB51 - Adone, Rosanna (American Society for Microbiology, 1999)
The live attenuated Brucella abortus strain RB51 is a rifampin-resistant, lipopolysaccharide (LPS) O-chain-deficient mutant of virulent B. abortus 2308. The reduced O-chain content in RB51 prevents this bacterium from inducing antibodies detectable by the conventional serologic tests for bovine brucellosis diagnosis that mainly identify antibodies to LPS. The absence of available serologic tests for RB51 also complicates the diagnosis of possible RB51 infections in humans exposed to this strain. The purpose of this study was to evaluate the suitability of a complement fixation (CF) test performed with the rough strain B. abortus RB51, previously deprived of anticomplementary activity, in detecting anti-B. abortus RB51 antibodies in cattle and sheep experimentally vaccinated with this strain. The results of this study showed that a CF test with RB51 as the antigen is able to specifically detect antibodies following RB51 vaccination in cattle and sheep. In addition, this method could be a useful tool for detecting B. abortus RB51 infection in humans.